MOBICAT: a model-driven engineering approach for automatic GUI code generation for Android applications - Zafar, Haroon; Ur Rehman Khan, Saif; Mashkoor, Atif; Nisa, Habib Un (Frontiers in Computer Science, 2024)
Mobile applications have become indispensable in our daily lives. However, mobile application development faces several challenges, including limited resources, budget, and time to market. The current state of the practice intends to develop the Graphical User Interface (GUI), business logic, and the controller class separately, which is a time-consuming and error-prone process. The generation of GUI is a significant concern in the development of mobile applications. This work presents a model-driven engineering approach for automatic GUI code generation for Android applications, which intends to address the above-mentioned challenges in mobile app development. The proposed approach involves modeling domain-specific features of mobile applications and capturing requirements using UML diagrams that lead to auto-mated GUI generation and controller class creation. We develop a Model-Based GUI Code Generator (MOBICAT) tool to provide automation support to the proposed approach. The efficacy of the MO-BICAT tool is evaluated by comparing it with the baseline techniques using three open-source applications. The results indicate that the MOBICAT tool significantly outperforms the baseline techniques by attaining improved execution progress, effectively reducing development cost and effort.